Acute Mild Moderate Unexplained Pancreatitis: Which Treatment? - De Biasio, Pasquale; Forlano, Immacolata; Lapolla, Francesco; Giambavicchio, Libero Luca; Neri, Vincenzo (JOP. Journal of the Pancreas, 2013)
Context Unexplained pancreatitis actually remain a diagnostic and therapeutic challenge. Objective The aim of this study is to define a possible therapeutic program for mild-moderate acute pancreatitis, most often recurrent, which at the end of the diagnostic process remain with an undefined etiology. Methods In the period 2011-2012 we observed 64 acute pancreatitis (AP): 52 mild-moderate and 12 severe AP. Etiological data: 39 biliary AP; 5 biliary AP in alcoholic chronic pancreatitis; 20 unexplained recurrent AP. At the end of the clinical and instrumental evaluation of the 20 unexplained AP, we had 6 patients with biliary sludge, 4 microlithiasis, 4 sphincter of Oddi dysfunction, 6 AP remain undefined. Results Among 20 patients with recurrent AP unexplained at the admission, we performed 10 videolaparocholecystectomies (VLC), 2 open cholecystectomies, 4 ERCP/ES in patients undergone to previous cholecystectomy, and 4 patients refused surgery. In particular in 6 patients with unexplained acute pancreatitis, 4 VLC and 2 ERCP/ES were performed. Follow up after 6 months was negative for further recurrence in all patients. Conclusion The recurrence of unexplained acute pancreatitis with a non predictable severity evolution is due to the persistence of the bilio-pancreatic flux obstacle, in most cases (80%) related to microlithiasis. After the complete diagnostic process which may exclude other causes, it is proposable to perform a cholecystectomy and/or ERCP/ES to define empirical in few cases.